Absence of autophagy promotes apoptosis by modulating the ROS-dependent RLR signaling pathway in classical swine fever virus-infected cells. Issue 10 (2nd October 2016) - Pei, Jingjing; Deng, Jieru; Ye, Zuodong; Wang, Jiaying; Gou, Hongchao; Liu, Wenjun; Zhao, Mingqiu; Liao, Ming; Yi, Lin; Chen, Jinding
ABSTRACT: A growing number of studies have demonstrated that both macroautophagy/autophagy and apoptosis are important inner mechanisms of cell to maintain homeostasis and participate in the host response to pathogens. We have previously reported that a functional autophagy pathway is trigged by infection of classical swine fever virus (CSFV) and is required for viral replication and release in host cells. However, the interplay of autophagy and apoptosis in CSFV-infected cells has not been clarified. In the present study, we demonstrated that autophagy induction with rapamycin facilitates cellular proliferation after CSFV infection, and that autophagy inhibition by knockdown of essential autophagic proteins BECN1/Beclin 1 or MAP1LC3/LC3 (microtubule-associated protein 1 light chain 3) promotes apoptosis via fully activating both intrinsic and extrinsic mechanisms in CSFV-infected cells. We also found that RIG-I-like receptor (RLR) signaling was amplified in autophagy-deficient cells during CSFV infection, which was closely linked to the activation of the intrinsic apoptosis pathway. Moreover, we discovered that virus infection of autophagy-impaired cells results in an increase in copy number of mitochondrial DNA and in the production of reactive oxygen species (ROS), which plays a significant role in enhanced RLR signaling and the activated extrinsic apoptosis pathway in cultured cells. Collectively, these data indicate that CSFV-induced autophagy delays apoptosis by downregulating ROS-dependent RLR signaling and thus contributes to virus persistent infection in host cells.